EFFECT OF PATIENT’S GENDER ON THE CALCULATION OF TIME-INTEGRATED ACTIVITY COEFFICIENT IN RADIONUCLIDE THERAPY: STUDY WITH NON-LINEAR MIXED-EFFECTS MODEL - Assyifa Rahman Hakim; Fira Dwi Ananda; Indra Budiansah; Rien Ritawidya; Deni Hardiansyah (Joint Prosiding IPS dan Seminar Nasional Fisika, 2026)
Purpose: This study investigates the influence of patient gender on the calculation of the Time-Integrated Activity Coefficient (TIAC) in radionuclide therapy. Methods: Kidney biokinetic data (PMID: 33443063) from 10 patients (6 males and 4 females) treated with [¹⁷⁷Lu]Lu-DOTATATE were analysed. A bi-exponential function was used to model both uptake and clearance phases. The reference TIAC (rTIAC) was obtained by fitting the bi-exponential parameters to the complete dataset using a Non-Linear Mixed-Effects Model (NLMEM). To assess the impact of gender, separate NLMEM fits were performed for male and female subgroups to generate estimated TIACs (eTIACs). rTIAC and eTIAC values were compared using the Relative Deviation (RD) and the Root-Mean-Square Error (RMSE). Gender was considered influential if RD or RMSE exceeded 27%. Results: For male patients, the RD was −4.1% ± 7.2% and the RMSE was 8.3%. For female patients, the RD was 5.2% ± 7.8% and the RMSE was 9.4%. Conclusions: Based on the analysed [¹⁷⁷Lu]Lu-DOTATATE biokinetic data, gender does not appear to be a major determinant in TIAC calculation. The deviations between rTIAC and eTIAC remain within an acceptable range for both male and female patients.